Key parameters for the successful implementation of sri lanka's national resettlement policy in an urban context - Rupasinghe, S.R. (My University, 2008)
In the 1990's many people became casualties of unplanned development induced resettlement. A majority of such families live in the urban context and continue to face various types of improvishments. They have no stable income and poverty is a main cause for urban environmental degradation. Settlements occu1?iedby such communities are located throughout the City of Colombo but mainly in low lying lands in congested pockets. Land titling has not be done and basic urban infrastructure facilities such as water supply, waste water and storm water drainage facilities, sewer lines and space for solid waste disposal have been at a minimum. The local authorities are reluctant to support such communities due to high investment and most families continue to live in poverty, with such slum and shanties being notorious for high crime ratesandenvironmentaleye sores.Eventuallymakinga big negativeimpactonthe livesof urban . middleclass. In 2001, the introduction of the National Involuntary Resettlement Policy (NIRP) in Sri Lanka, requiredthat development induced resettlement projects use the policy as a guideline to ensure persons affected by the project would be either of a similar economic and social status or higher than before resettlement. Compensation payments were required to be at present market value and project implementation agencies were required to do extensive community development, mobilization and awareness so that those affected by the development would be eventual 'winners'. It was required to empowerthe project affected persons to ensure they were converted in to real beneficiaries and ensure social, economic safeguards were in place. The Lunawa Environmental Improvement and Community Development Project (LEI&CDP) was initiated in 2001 with a view to minimize the flood damage in the Lunawa catchment and improve the overall environment in the said areas. As the number of directly affected persons were over 100 families, the National Involuntary Resettlement Policy was used to develop resettlementguidelines and action plans for the Project area in the Lunawa catchment. Thus commenced a carefully planned and formulated resettlement process where transparency, and active involvement of the affected communities were considered priority. For the first time in Sri Lanka a policy allowed for families who had no ownership to land to be eligible for a minimum 2 perch plot of land and Rs.424,OOOas compensation to build their house. Unlike in previous resettlement projects implemented during the 1990s, there has been minimal public protest and objections towards the LEI&CDP, with improved status of middle class urban relocationareas developed in the Lunawa Catchment. Fromthe experience of implementing the LEI&CDP, 3 parameters were identified as being the main attributes to the success of this urban resettlement project. These were not only social and economicrelated but also include that concerning the environment and habitat.